Gas exchange in ‘BRS Princesa’ banana (Musa spp.) under partial rootzone drying irrigation in the north of Minas Gerais, Brazil - Marcelo Rocha dos Santos; Sérgio Luiz Rodrigues Donato; Alessandro de Magalhães Arantes; Eugênio Ferreira Coelho; Pollyanna Mara de Oliveira (Acta Agronómica, 2017)
This research aimed to evaluate physiological characteristics of 'BRS Princesa' banana under Partial Rootzone Drying irrigation, PRD. The five treatments, 1 - 50% of reduction in water depth (WD) with a frequency alternation of irrigation side (FA) of seven days during the whole production cycle; 2 - 50% of WD and FA of 14 days in the cycle; 3 - 50% of WD and FA of 21 days; 4 - 50% of WD with a fixed irrigation (only one lateral line on one side of the plant); and 5 - full irrigation (two lateral lines with open shutoff valve) throughout the cycle, they were arranged in a randomized block design with five replicates. There is a reduction in photosynthetic rates and water use efficiency as a result of enzymatic impairment or stomatal closure, due to the increased of leaf temperature. The stomatal conductance - gs was lower in plants irrigated with 50% of ETc with fixed irrigation in one side of the plant. Even with water deficit in the soil, using the PRD with 50% of ETc, Photosynthesis - A Transpiration - E; Leaf temperature - Tleaf, internal concentration of CO2 - Ci; stomatal conductance - gs; photosynthetically active radiation - Qleaf; carboxylation efficiency - A/Ci; Quantum efficiency of Photosynthesis - A/Qleaf; and instantaneous water use efficiency - WUE 'BRS Princesa' banana were similar among strategies, highlighting the possibility of use of the irrigation management technique with PRD, saving water, and no physiological changes in the plants.